ENTREPRENEURSHIP, INFORMATION, AND GROWTH. (7th October 2014) - Bunten, Devin; Weiler, Stephan; Thompson, Eric; Zahran, Sammy
ABSTRACT We examine the contribution to economic growth of entrepreneurial marketplace information within a regional endogenous growth framework. Entrepreneurs are posited to provide an input to economic growth through the information revealed by their successes and failures. We empirically identify this information source with the regional variation in establishment births and deaths. To account for the potential endogeneity caused by forward‐looking entrepreneurs, we utilize instruments based on historic mining activity. We find that the information spillover component of local establishment birth and death rates have significant positive effects on subsequent entrepreneurship and employment growth for U.S. counties and metropolitan areas.